Peran Mediasi Job Satisfaction pada Hubungan Employee Engagement Terhadap Organizational Citizenship Behavior (OCB) di SMK Negeri 1 Ende - Albertus Jao Ndu; Avianita Rachmawati; Imaculata Fatima (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to find out whether employee engagement has an effect on organizational citizenship behavior, employee engagement has an effect on job satisfaction, job satisfaction has an effect on organizational citizenship behavior and job satisfaction mediates a direct effect on organizational citizenship behavior in teachers at SMK N 1 Ende. This research used a descriptive and causal approach with a sample size of 136 teachers at SMKN 1 Ende. Data collection techniques were obtained from questionnaires distributed to respondents and data testing using the SPSS version 26 application. The research results of the variables employee engagement (X), job satisfaction (Z) and organizational citizenship behavior (Y) show that employee engagement positive influence on organizational citizenship behavior, employee engagement positive influence on Job Satisfaction, Job Satisfaction positive influence on Organizational Citizenship Behavior, Job Satisfaction mediating direct influence employee engagement to Organizational Citizenship Behavior gteacher at SMKN 1 Ende. The results of this research explain that Job Satisfaction mediating direct influence employee engagement to Organizational Citizenship Behavior gteacher at SMKN 1 Ende.